Women's knowledge, attitudes and practices (KAP) relating to breast and cervical cancers in rural Zimbabwe: a cross sectional study in Mudzi District, Mashonaland East Province - Lovemore Makurirofa; Priscilla Mangwiro; Victoria James; Amos Milanzi; Junior Mavu; Michael Nyamuranga; Sydney Kamtauni (BMC, 2019)
Abstract Background Breast and cervical cancers constitute the most common cancers among women in sub-Saharan Africa. In Zimbabwe, cervical cancer accounts for more than a third of all cancers among women of African descent. Cancer knowledge levels, attitudes and practices of people in different sections of society should be assessed in order to guide current cancer interventions. This study aimed to assess breast and cervical cancer knowledge, attitudes and practices of women of reproductive age, in Mudzi District, Republic of Zimbabwe. Methods A cross-sectional community-based survey was conducted. A total of 409 survey household questionnaires were administered to women of reproductive age (15-49 years) in 2014. Results A total of 409 respondents were interviewed. Nearly 85% of respondents had heard of cancer. 34.2% did not know of any cervical cancer risk factors and 51% were not familiar with the signs and symptoms of cervical cancer. Fifty five percent (55%) had not discussed cancer issues with partners in the past 12 months, and only 27.4% had discussed cancer issues with partners at all. Most of the respondents (96.2%) had never undergone cervical cancer screening. The majority of the respondents (70.8%) had never discussed breast cancer issues with community members. About 70% had never discussed cervical cancer issues with community members. Conclusions This study revealed a lack of awareness and comprehensive knowledge about breast and cervical cancer. It also revealed low self-risk perception, low uptake of cancer early detection services and low capacity of the local health institution in offering cancer services. It is recommended that the scaling-up of cancer information, dissemination, and early detection services must be prioritised, including training of local health institutions.